2022
DOI: 10.1002/jad.12026
|View full text |Cite
|
Sign up to set email alerts
|

Assessing feasibility of an adolescent relationship abuse prevention program for girls

Abstract: Introduction Sexual violence and relationship abuse are prevalent among adolescents and programs promoting gender equity, reproductive justice, and healthy relationships are key strategies for prevention. While such “gender transformative” approaches appear promising for boys, they have not been evaluated among girls. This study assessed the feasibility of this community‐based program, called Sisterhood 2.0, among girls in socially disadvantaged urban neighborhoods in Pittsburgh, Pennsylvania. Methods This qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The findings from the current study highlight that there are significant differences in experiences with ARA, gender attitudes, and condom and contraception self efficacy among girls living in poverty (reflected in the lower levels of parental education). Notably, high levels of experiences with ARA tended to cluster with lower gender equitable attitudes and poor condom and contraception self efficacy, suggesting that trauma-focused interventions for youth with prior experiences with partner or relationship violence that intentionally address gender norms within dating and sexual relationships may be especially relevant (“A Feasibility Trial of Sisterhood 2.0”(Clinical Trials Nct, 2020; HIll et al, 2022; Reidy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from the current study highlight that there are significant differences in experiences with ARA, gender attitudes, and condom and contraception self efficacy among girls living in poverty (reflected in the lower levels of parental education). Notably, high levels of experiences with ARA tended to cluster with lower gender equitable attitudes and poor condom and contraception self efficacy, suggesting that trauma-focused interventions for youth with prior experiences with partner or relationship violence that intentionally address gender norms within dating and sexual relationships may be especially relevant (“A Feasibility Trial of Sisterhood 2.0”(Clinical Trials Nct, 2020; HIll et al, 2022; Reidy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Data were from the baseline assessment of a quasi-experimental pilot study examining the effectiveness of an ARA and SV prevention program for high school-aged adolescent girls (“A Feasibility Trial of Sisterhood 2.0”)(Clinical Trials Nct, 2020)(HIll et al, 2022). Participants were ages 13–19 years recruited between 2017–2019 through community organizations from neighborhoods in Pittsburgh, Pennsylvania (Eugene et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Of the 44 articles included, nearly half of them aimed at evaluating outcomes only ( n = 20; 45.5%) [ 42 , 47 , 48 , 50 , 52 , 55 , 58 , 61 , 63 , 64 , 66 69 , 71 , 77 79 , 82 , 83 ], whereas 18 described outcome and process evaluation (40.9%) [ 41 , 43 46 , 49 , 51 , 53 , 54 , 57 , 59 , 62 , 70 , 72 74 , 81 , 84 ], and 6 focused on process evaluation solely ( n = 6; 13.6%) (56, 60, 65,75, 76, 80). However, only a few studies explicitly used the terms ‘process evaluation’ ( n = 14) and/or ‘outcome evaluation’ ( n = 4) to describe their evaluation strategies.…”
Section: Strategies and Methods Of Evaluationmentioning
confidence: 99%
“…In terms of methods used, in 25 publications including 33 different study designs quantitative methods were reported ( n [ 41 , 46 50 , 54 , 55 , 58 , 61 , 64 , 66 69 , 71 , 75 79 , 81 84 ], 16 publications reported on 27 mixed method designs ( n ) [ 42 45 , 51 53 , 56 , 57 , 60 , 62 , 63 , 70 , 73 , 74 , 80 ] and 3 publications reported on 5 qualitative methods based designs [ 59 , 65 , 72 ] (Table 5 ).…”
Section: Strategies and Methods Of Evaluationmentioning
confidence: 99%
See 1 more Smart Citation